VIBRATIONAL SPECTROSCOPY OF BETA-EUCRYPTITE (LIALSIO4): OPTICAL PHONONS AND PHASE TRANSITION(S) - Zhang M.; Salje E.K.H.; Xu H.; Heaney P.J. (My University, 2003)
The structural behavior of β-eucryptite (LiAlSiO4) has been investigated using infrared (IR) spectroscopy over a temperature range of 20 to 900 K and FT-Raman spectroscopy at room temperature. IR reflectance measurements show that β-eucryptite possesses high reflectivity in the far-IR region, as is consistent with its reported superionic conductivity along the c-axis. On heating, the Li-related IR bands near 246 and 300 cm−1 (with A 2 symmetry) broadened and weakened dramatically, presumably as a result of Li+ positional disordering along the structural channels parallel to c. The disordering process appears to induce a framework distortion, as is evidenced by the broadening of some vibrations of Si(Al)–O with increasing temperature. A change in slope in the temperature dependence of the phonon frequency near 300 cm−1 and the linewidth of the 760 cm−1 band at ∼715 K indicates that Li becomes completely disordered above this temperature. In addition, the temperature dependence of the linewidth for the 760 cm–1 band exhibits an additional change in slope at 780 K, implying the existence of an intermediate state within this temperature range. The detailed structure of this intermediate phase, however, needs further study. Our IR data provide no indication of structural changes between room temperature and 20 K.
Keywords: β-eucryptite; Infrared spectroscopy; Raman spectroscopy; Phase transition; Li disorder